The utility of lumbar spine trabecular bone score and femoral neck bone mineral density for identifying asymptomatic vertebral fractures in well-compensated type 2 diabetic patients. Issue 1 (January 2016) - Zhukouskaya, V.; Ellen-Vainicher, C.; Gaudio, A.; Privitera, F.; Cairoli, E.; Ulivieri, F.; Palmieri, S.; Morelli, V.; Grancini, V.; Orsi, E.; Masserini, B.; Spada, A.; et al.
Abstract Summary The objective of the study was to evaluate the usefulness of trabecular bone score (TBS) and bone mineral density (BMD) for identifying vertebral fractures (VFx) in well-compensated type 2 diabetic (T2D) patients. TBS and femoral neck BMD below certain cutoffs may be useful for identifying VFx in well-compensated T2D patients. Introduction In T2D, the prevalence of VFx is increased, especially in poorly compensated and complicated diabetic patients. The possibility of predicting the fracture risk in T2D patients by measuring BMD and TBS, an indirect parameter of bone quality, is under debate. Therefore, the objective was to evaluate the usefulness of TBS and BMD for identifying VFx in well-compensated T2D patients. Methods Ninety-nine T2D postmenopausal women in good metabolic control (glycosylated haemoglobin 6.8 ± 0.7 %) and 107 control subjects without T2D were evaluated. In all subjects, we evaluated the following: the BMD at the lumbar spine (LS) and the femoral neck (FN); the TBS by dual X-ray absorptiometry; and VFx by radiography. In T2D subjects, the presence of diabetic retinopathy, neuropathy, and nephropathy was evaluated. Results T2D subjects had increased VFx prevalence (34.3 %) as compared to controls (18.7 %) (p = 0.01). T2D subjects presented higher BMD (LS −0.8 ± 1.44, FN −1.06 ± 1.08), as compared to controls (LS −1.39 ± 1.28, p = 0.002; FN −1.45 ± 0.91, p = 0.006, respectively). TBS was not different between diabetics and controls. In fractured T2D patients, LS-BMD, FN-BMD, and TBS were reduced (−1.2 ± 1.44; −1.44 ± 1.04; 1.072 ± 0.15) and the prevalence of retinopathy (15.4 %) was increased than in nonfractured T2D subjects (−0.59 ± 1.4, p = 0.035; −0.87 ± 1.05, p = 0.005; 1.159 ± 0.15, p = 0.006; 1.8 %, p = 0.04, respectively). The combination of TBS ≤1.130 and FN-BMD less than −1.0 had the best diagnostic accuracy for detecting T2D fractured patients (SP 73.8 %, SN 63.6 %, NPV 78.9 %, PPV 56.8 %). Conclusions TBS and FN-BMD below certain cutoffs may be useful for identifying VFx in well-compensated T2D patients.